Program Kemitraan Masyarakat (PKM) Kelompok PKK di Desa Kayuuwi 1 Kecamatan Kawangkoan Barat Kabupaten Minahasa (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Abstract Kayuuwi 1 village is located at an altitude of 700 meters above sea level, far from the coast, so they often consume processed fish or better known as Cakalang fufu, anchovies (white fish), salted fish which are sold in the Kawangkoan market. During Covid 19, various changes occurred where traveling traders from the Amurang coast when fish were abundant selling fresh marine fish, such as skipjack, baby tuna, or reef fish. So that housewives who are members of the PKK group need to get counseling on how to choose fresh and quality fish and how to take advantage of existing opportunities such as making cooked processed fish or making good and quality fish balls, providing awareness to the public about the importance of hygiene in food processing so as to reduce health risks for humans, provide knowledge and skills to partners about simple bookkeeping, so as to improve their skills in entrepreneurship, improve family nutrition, as well as improve the family economy. The methods used in this activity are counseling, empowerment, training and mentoring for PKK mothers in Kayuuwi village. in Group. From this activity, it was concluded that the PKK group in Kayuuwi 1 village was able to increase insight, knowledge, attitudes, and motivation as well as increase skills.